If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2=v-3/3
We simplify the equation to the form, which is simple to understand
2=v-3/3
We move all terms containing v to the left and all other terms to the right.
-1v=-1-2
We simplify left and right side of the equation.
-1v=-3
We divide both sides of the equation by -01 to get v.
v=3
| 1/5x-3=4 | | -5w^2+8=0 | | T/-2=18 | | 2(2x+5)-3=-3(x-1) | | 3x-2/3=7 | | 2x+9y-36=180 | | c(x)=x-4/x^2-16 | | -17=n-20 | | 4nm-4m=8 | | 17+2n=2n+21 | | 24=(3-n)+5 | | 1w=-11 | | x-18.1=-0.7 | | 0.01(1)+0(-0.5)=0.02(-0.5)+1 | | 6x+55=3x+244 | | m^3=8/125 | | j-3/2=2 | | -8+3.5=1-4(3.5) | | -3n+18=-6(n+1) | | 12x-34=46+7x | | 12b=.2 | | (6g-9)+1/3(15-9g)= | | 12+3d=d | | 5.7+b=23 | | -4x+82=-86-10x | | 25=n-(3) | | R^2=-96 | | (0.01)(1)+0x=0.02(x+1) | | 24x^2-58x+40=7 | | 2/3y-12 | | 17=-d | | -2=j-3/2 |